Daya Terima Biskuit dengan Modifikasi Tepung Biji Nangka, Tepung Kacang Merah dan Tepung Pisang serta Kontribusinya Terhadap Kecukupan Zat Besi Remaja di SMAN 3 Kendari - Wulandari, Agnes Sri; Ananda, Siti Hadrayanti; Abadi, Ellyani (Jurnal Gizi Ilmiah, 2024)
Agnes Sri Wulandari, Acceptability of Biscuits with Modification of Jackfruit Seed Flour, Red Bean Flour and Banana Flour and Its Contribution to Iron Adequacy of Adolescents at SMAN 3 Kendari, Siti Hadrayanti Ananda, Ellyani Abadi Jackfruit seed flour, kidney bean flour and banana flour can be processed into various types of products that can contribute nutrients such as iron in adolescents who are in the growth period. One such product is biscuits. The purpose of this study is to determine acceptability based on organoleptic properties which include color, taste, aroma and texture which are tested with a questionnaire with hedonic assessment and its contribution to the iron adequacy of adolescents in SMAN 3 Kendari.This study is a type of descriptive research with a quantitative approach method in making biscuits with modifications of jackfruit seed flour, red bean flour and banana flour using a complete random design (RAL) with 3 treatments (70:40:40, 40:70:40, 40:40:70). Research on the acceptability test of biscuits with flour modification was carried out at SMAN 3 Kendari, while research on the nutritional content of biscuits was carried out at the Food and Drug Agency (BPOM) of Kendari City.The results of the study showed that based on the organoleptic results of the color, taste and texture of the most preferred biscuits were biscuits with A3 treatment (40:40:70) and the preferred aroma was biscuits with A1 treatment (70:40:70). The addition of jackfruit seed flour, red bean flour and banana flour in making biscuits has an iron content of 24,0 milligrams per 100 grams of biscuits. And donate 93,3% of the total daily iron needs of 16-17-year-old adolescents.Biscuits are recommanded to consumers to make these biscuits as an alternative substitute for snacks to meet the iron requirements of adolescents.further research is also needed into the manufacture of jackfruit seed flour, red been flour and banana flour as well as the shelf life of each flour. Keywords: Biscuits, Jackfruit Seeds, Red Beans, Iron